A new species of Habenaria (Orchideae, Orchidoideae, Orchidaceae) from the Amazon and Orinoco regions of Colombia and Venezuela - Lozano-Cifuentes, David; Ríos-Cervera, Jorge; Cruz-Lustre, Gabriela; Batista, João A. N. (Phytotaxa, 2025)
Habenaria granitica, a new species from Colombia and Venezuela is described, illustrated, and compared with morphologically similar or previously misidentified taxa. All known records are from the Amazon and Orinoco regions, indicating that the species is restricted to these areas, where it invariably grows associated with granite outcrops, amid areas of savanna or lowland moist forests. Habenaria granitica has been known since 1957, but was mainly misidentified with H. dusenii, from which it differs by shorter pedicel (9.8–10.4 mm long vs. 15–28 mm long), shorter spur (21–26 mm long vs. 29–39 mm long), separate pollinaria (vs. joined by viscidium), vegetative morphology, with patent and usually basal leaves (vs. distributed along the stem and adpressed to it), geographic distribution and for growing in granite outcrops (vs. wet meadows). Habenaria granitica adds yet another species endemic to the granite outcrops of the Orinoco and Amazon basins in Colombia and Venezuela.